Development of a fluorine-18 radiolabelled fluorescent chalcone: evaluated for detecting glycogen - Louis Allott; Diana Brickute; Cen Chen; Marta Braga; Chris Barnes; Ning Wang; Eric O. Aboagye (SpringerOpen, 2020)
Abstract Background Glycogen is a multibranched polysaccharide of glucose produced by cells to store energy and plays a key role in cancer. A previously reported fluorescent probe (CDg4) was shown to selectively bind glycogen in mouse embryonic stem cells, however the molecule was not evaluated in cancer cells. We report the synthesis and biological evaluation of a dual-modality imaging probe based on CDg4, for positron emission tomography (PET) and fluorescence microscopy. Results A fluorine-18 radiolabelled derivative of CDg4, ([ 18 F]5) for in vivo quantification of total glycogen levels in cancer cells was developed and synthesised in 170 min with a non-decay corrected radiochemical yield (RCY n.d.c) of 5.1 ± 0.9% (n = 4) in > 98% radiochemical purity. Compound 5 and [ 18 F]5 were evaluated in vitro for their potential to bind glycogen, but only 5 showed accumulation by fluorescence microscopy. The accumulation of 5 was determined to be specific as fluorescent signal diminished upon the digestion of carbohydrate polymers with α-amylase. PET imaging in non-tumour bearing mice highlighted rapid hepato-biliary-intestinal elimination of [ 18 F]5 and almost complete metabolic degradation after 60 min in the liver, plasma and urine, confirmed by radioactive metabolite analysis. Conclusions Fluorescent compound 5 selectively accumulated in glycogen containing cancer cells, identified by fluorescence microscopy; however, rapid in vivo metabolic degradation precludes further investigation of [ 18 F]5 as a PET radiopharmaceutical.